NASPGHAN Nutrition University (N2U): A Survey of its Efficacy as Continuing Nutrition Education for North American Society of Pediatric Gastroenterology, Hepatology, and Nutrition. Issue 2 (August 2020) - Larson-Nath, Catherine; Goday, Praveen S.; Fiechtner, Lauren; Mangalat, Nisha; Schwartz, Sally; Scheimann, Ann; Sentongo, Timothy; Turner, Justine M.
Abstract : ABSTRACT: The North American Society of Pediatric Gastroenterology, Hepatology, and Nutrition (NASPGHAN) developed NASPGHAN Nutrition University (N2U) in 2012 to improve nutrition education for pediatric gastroenterology providers. A total of 543 providers (physicians, registered dietitians, and advanced practice nurses) have applied to N2U and 285 have attended this 2-day course. We used survey methodology to compare attendees to applicants who did not attend. Course attendees reported more confidence than nonattendees in the nutritional management of patients with short bowel syndrome, feeding disorders, and gastrointestinal allergies, even though they were seen at similar frequency in both groups. Eighty-eight percent of attendees disseminated the information they learned at N2U through venues such as grand rounds or guideline/policy development. These results demonstrate the benefit of N2U in enhancing nutrition education for pediatric gastroenterology practitioners.